2020
DOI: 10.1590/1981-5271v44.1-20190218.ing
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Settlement of Medical Residences in the State of Tocantins in the Period 2013-2017

Abstract: Introduction: The accomplishment of medical residency (MR) is a type of qualification considered to be the “gold standard” for medical specialization. Understanding whether there is actually greater professional settlement or not stimulated by MR and which factors hinder or contribute to the physician’s permanence in that place, are important information for the structuring of medical residency and health system programs. The aim of this study was to evaluate the prevalence of settlement of medical residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…4 A pilot study conducted in the state of Tocantins that analyzed the prevalence of remaining in the state between 2013 and 2017 revealed that 65.9% of residents stayed in Tocantins. 5 Another complete survey considering only the years 2013 and 2014 revealed that 50% of graduating residents remained in the state. 3 These data demonstrated that medical residents' decisions on where to settle are based on numerous factors that go beyond the increase in vacancies, such as working conditions, sex, remuneration, city of origin, family and proximity to large urban and economic centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A pilot study conducted in the state of Tocantins that analyzed the prevalence of remaining in the state between 2013 and 2017 revealed that 65.9% of residents stayed in Tocantins. 5 Another complete survey considering only the years 2013 and 2014 revealed that 50% of graduating residents remained in the state. 3 These data demonstrated that medical residents' decisions on where to settle are based on numerous factors that go beyond the increase in vacancies, such as working conditions, sex, remuneration, city of origin, family and proximity to large urban and economic centers.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study conducted in the state of Tocantins that analyzed the prevalence of remaining in the state between 2013 and 2017 revealed that 65.9% of residents stayed in Tocantins. 5 Another complete survey considering only the years 2013 and 2014 revealed that 50% of graduating residents remained in the state. 3 …”
Section: Introductionmentioning
confidence: 99%